2006
DOI: 10.1007/s10820-006-9008-y
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Scale Chemo-mechanics of Silica: Nano-rod Deformation and Water Reaction

Abstract: The notion of bond rupture as the initiation event leading to mechanical failure in a material system is well known. Less recognized but no less valid is that bond strain also fundamentally affects the chemical reactivity of the atoms involved in the bonding. This dual role of bond strain is clearly brought out in the present simulations. Stress-strain response of dry silica to the point of structural instability is studied using a classical inter-atomic potential model, whereas transition-state pathway sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…[48] Future research lies in addressing the impact of a larger number of hierarchy levels on the mechanical properties of silica nanostructures and the effect of water and hydrogen termination on hierarchical silica. Interestingly, a previous study used the semiempirical QM methods, PM3, and PM5 along with the BKS potential and found that water reduces the critical stress and failure strain of silica nanorods, [42] and it is expected that similar effects might be crucial for the system considered here as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[48] Future research lies in addressing the impact of a larger number of hierarchy levels on the mechanical properties of silica nanostructures and the effect of water and hydrogen termination on hierarchical silica. Interestingly, a previous study used the semiempirical QM methods, PM3, and PM5 along with the BKS potential and found that water reduces the critical stress and failure strain of silica nanorods, [42] and it is expected that similar effects might be crucial for the system considered here as well.…”
Section: Discussionmentioning
confidence: 91%
“…For example, silica nanorods modeled using the Beest-Kramer-Santen (BKS) and Tsuneyuki-Tsukada-Aoki-Matsui (TTAM) potentials showed a softening effect when under tension. [41,42] Another study conducted ab initio simulations using the projector-augmented-wave (PAW) method and found a pressure dependence on the bulk modulus of silica. [43] Experimental measurements of silver nanowires loaded in tension along the [0 1 1] direction found a stiffening behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The BKS interatomic pair-potential has been extensively used in studies of the dynamics and structural properties of silica in many forms and conditions. 8,10,[29][30][31] A. Bulk silica and silica nanowire model creation A bulk silica glass model (14.32 Â 14.32 Â 14.32 nm 3 ) containing 192 000 atoms was first prepared using a wellestablished melt-quench procedure, 9,10,20 then silica NWs of a fixed length and different diameters were carved out from the bulk structure.…”
Section: Simulation and Analysis Methodsmentioning
confidence: 99%
“…Stress corrosion cracking in quartz involves the rupture of strained Si–O bonds at the crack tip and proceeds at the molecular level by similar pathways to dissolution (Dove, ). Furthermore, strained Si–O bonds are more reactive than unstrained ones, as shown by molecular dynamic simulations (Colombi Ciacchi et al, ; Lindsay et al, ; Silva et al, ; Y.‐A. Zhang et al, ).…”
Section: Discussionmentioning
confidence: 97%